Gaya Berkendara dalam Iklan: Antara Representasi Ketangguhan dan Kecerobohan - Ivan Kurniawan; Irma Rochmawati (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2018)
Nowadays, transportation needs in urban area are increasing continuously. This certainly has an impact on the marketing policy of transportation producers, including the motorcycle industry. Among them, the series of television commercials ads distributed by Yamaha Motor Indonesia in 2016 are the most interesting; because of the way advertising through visuals have similarities. Despite the fact that these ads contain different product information and motorcycle genres, this condition has influenced the viewer’s perception of the company’s image through the products in the ads and how the products were treated. Visual representation studies of Yamaha ads are very important, especially related to the perception of motorcycle users in the context of the driving style that was presented in advertisements. This research uses descriptive research method by using visual and content analysis approach. The study will also reveal public perceptions involving respondents in the age of 18 to 30 years as the age range that dominate the purchase figure in Indonesia. The study concluded that Yamaha is trying to give an idea of the toughness of its engine technology, but is represented in advertisements through ‘aggressive’ and ‘fast’ driving styles. The perception of the driving force captured by society is an aggressive and arrogant driving style.